Gabbro aggregate rolled concrete and preparation method thereof
By using medium-thermal silicate cement, fly ash and graded gabbrostone aggregates, combined with retarding high-efficiency water reducer and alkyl alcohol ether gas induction agents, the problems of low utilization rate and difficulty in processing in rolled concrete are solved, and efficient and economical concrete preparation is achieved, and performance meets standards.
Patent Information
- Application Number
- CN202211637430.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-16
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-12-16
AI Technical Summary
In the prior art, the application of gabbrostone aggregate in rolled concrete has problems such as low utilization rate, long processing time, high energy consumption, difficulty in handling waste materials, and low strength and homogeneity.
Medium-heat silicate cement, fly ash and graded gabbro-coarse aggregates are used, combined with retarding high-efficiency water reducer and alkyl alcohol ether gas induction agents, to control the hydration temperature rise and alkali content of cement, optimize the aggregate grading and stone powder content to improve the strength, stability and frost resistance of concrete.
It realizes the efficient preparation of gabbro aggregate rolled concrete, improves the utilization rate of materials, reduces energy consumption and cost, and the strength, stability and frost resistance of concrete meet the specifications.
Smart Images

Figure BDA0004003398610000071 
Figure BDA0004003398610000072 
Figure BDA0004003398610000073
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete, in particular to a gabbro aggregate roller compacted concrete and a preparation method thereof. Background Art
[0002] In recent years, the quality and preparation technology of concrete raw materials such as cement, fly ash, and admixtures have shown a trend of gradual improvement. On the contrary, with the mining and consumption of high-quality natural aggregates and the increasing environmental protection requirements of the country for engineering construction, the development and preparation methods of artificial aggregates are far from meeting the development needs of advanced concrete technology. Aggregates account for more than 70% of concrete, and their quality largely determines the performance of concrete. Therefore, advanced rock aggregate development and utilization technology not only meets the three urgent concrete technology development requirements of economy, environmental protection, and technology, but also responds to the national policy indicators of energy conservation, emission reduction, and green production.
[0003] The Chinese patent with publication number CN105731919B discloses a super-high fly ash concrete, which relates to the field of building materials. The concrete includes the following components by weight: 48-60 parts of cement, 240-272 parts of fly ash, 656-696 parts of sand, 1293-1333 parts of crushed stone, 3.0-4.8 parts of water reducer, 0.18-0.26 parts of air entraining agent, and 80-90 parts of water. The crushed stone particle size added to the concrete is ≤40mm. The sand is medium sand. This invention combines the actual application and requirements of large-volume concrete engineering in water conservancy and hydropower engineering, uses ordinary silicate 42.5 cement and grade III fly ash, and adds high-performance concrete water reducer while keeping the slurry volume basically unchanged from the control group concrete (the concrete actually used in the dam uses medium-heat 42.5 cement + 35% grade I fly ash), which greatly reduces the water consumption of concrete, thereby reducing the water-cement ratio, so that the concrete strength and other properties can still be guaranteed when the fly ash content is as high as 80%, and its mechanical properties and deformation properties can meet the requirements of C18040 and below grades of concrete in water conservancy and hydropower engineering. This patent uses conventional crushed stone and sand, which is not suitable for other types of rocks.
[0004] Gabbro originates from the crust or upper mantle of basaltic magma and is formed by intrusion. It has a series of advantages such as wide distribution range, rich reserves, and low mining and transportation costs. However, since gabbro is usually fine-grained, massive or gabbro-structured (gabbro structure refers to the similarity of the automorphic structure of basic plagioclase and dark minerals such as olivine and pyroxene. It is either uniformly semi-automorphic grains, or all are anatomic grains, and the grain sizes are nearly equal, interlaced and arranged irregularly, which is called gabbro structure), after multiple crushing, it is mostly in the form of flakes or fine powders, with low strength and homogeneity. In addition, its main mineral composition contains a small amount of alkali-active components. There are still many technical difficulties in using it as a roller compacted concrete aggregate. Therefore, there is no report on roller compacted concrete with gabbro aggregate. At present, gabbro is mainly used as rough-processed monument material or decorative material after fine cutting and polishing, as well as for road asphalt admixture with fine aggregate, which has low requirements on aggregate strength and quality. The former has the disadvantages of low utilization rate, long processing time, high equipment requirements, weak economic benefits and environmental damage caused by waste treatment, while the latter requires multiple crushing, screening and cleaning steps of gabbro, with complicated processing technology and extremely high energy consumption. There are also problems such as low material qualification rate due to reduced aggregate strength caused by multiple crushing and impact, high environmental pressure on by-product treatment, time-consuming and labor-intensive, and low returns.
[0005] In the prior art, the hydration heat of medium heat Portland cement is 3d≤251kJ / kg and 7d≤293kJ / kg. Coarse aggregates are aggregates with a particle size greater than 5mm, such as sand and stone, which play a skeleton role in concrete. Fine aggregates are aggregates with a particle size of less than 5.00mm. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a gabbro aggregate rolled concrete and a preparation method thereof in view of the shortcomings of the existing technology. On the one hand, it solves the problems of poor application of gabbro, low utilization rate, difficult waste disposal, and time-consuming, labor-intensive and energy-consuming processing; on the other hand, it solves the technical difficulty that the characteristics of gabbro itself cannot easily meet the requirements of rolled concrete aggregate.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a gabbro aggregate roller compacted concrete comprises the following components in parts by weight: 65-105 parts of medium-heat silicate cement, 80-120 parts of fly ash, 1280-1680 parts of gabbro coarse aggregate, 700-900 parts of gabbro fine aggregate, 0.8-1.4 parts of water reducer, 0.1-0.2 parts of air entraining agent, and 73-113 parts of water;
[0008] The time for the hydration temperature rise of the medium-heat silicate cement to reach the temperature peak is 10-14 hours.
[0009] The rapid heat release of cement hydration leads to a decrease in the crack resistance of concrete and an excessively high internal temperature, which accelerates the alkali-aggregate reaction. Therefore, the present invention controls the time for the hydration temperature rise of the medium-heat Portland cement to reach the temperature peak to 10-14 hours, thereby improving the crack resistance of concrete and slowing down the alkali-aggregate reaction rate. After repeated tests and actual engineering applications, the present invention comprehensively considers factors such as the processing cost, utilization rate, energy consumption and time consumption of gabbro aggregates, so as to achieve the best workability, stability, strength, etc. of concrete. The test method or standard (hydration heat) for the hydration temperature rise of the medium-heat Portland cement to reach the temperature peak is tested according to GB / T12959.
[0010] Preferably, a gabbro aggregate roller compacted concrete comprises the following components in parts by weight: 68-96 parts of medium-heat Portland cement, 94-108 parts of fly ash, 1420-1560 parts of gabbro coarse aggregate, 782-846 parts of gabbro fine aggregate, 1.0-1.2 parts of water reducer, 0.1-0.2 parts of air entraining agent, and 86-98 parts of water;
[0011] The time for the hydration temperature rise of the medium-heat silicate cement to reach the temperature peak is 11-13 hours.
[0012] In a preferred embodiment of the present invention, the specific surface area of the medium-heat silicate cement is ≥250m 2 / kg, the alkali content of cement is controlled to be 0.3%-0.6%. Preferably, the specific surface area of the medium-heat silicate cement is ≥300m 2 / kg, the cement alkali content is controlled at 0.4%-0.45%.
[0013] The medium-heat silicate cement contains more micro-particles such as stone powder in the gabbro fine aggregate after crushing and grading optimization, and has a good void filling effect. The selection of coarse-grained cement not only conforms to the close packing theory, but also reduces cement grinding energy consumption and reduces costs. Fine cement hydration releases heat quickly, resulting in a decrease in the crack resistance of concrete and excessive internal temperature that accelerates alkali-aggregate reaction. Therefore, the specific surface area of the medium-heat silicate cement is controlled to be ≥250m 2 / kg. The cement alkali content of the medium-heat silicate cement is controlled so that the overall cement alkali content in the concrete is reduced.
[0014] In a preferred embodiment of the present invention, the mass proportion of Fe2O3 in the fly ash is 5%-8%, the mass proportion of Al2O3 is 12%-16%, and the mass proportion of CaO and MgO is 4%-6%. Preferably, the mass proportion of Fe2O3 in the fly ash is 5%-6%, the mass proportion of Al2O3 is 14%-15%, and the mass proportion of CaO and MgO is 3.5%-4.5%.
[0015] Under these conditions, fly ash can effectively inhibit the alkali activity of gabbro aggregate and reduce the problems of poor workability and deformation performance caused by poor aggregate shape, making it qualified to become RCC aggregate.
[0016] In a preferred embodiment of the present invention, the water reducer is a powdered slow-setting high-efficiency water reducer. Preferably, the water reducer has a fineness of 6%-7%, a slow-setting time of 320-370 min, a water reduction rate ≥15%, a water bleeding rate ratio of 35%-40%, a total alkali content of 15%-16%, and a shrinkage ratio ratio ≤125%.
[0017] By comparing the effects of a large number of water reducers, it was found that powdered water reducers with a fineness of 6%-7% can be evenly dispersed and stably exist in concrete for a long time, so the water-reducing effect and performance stability can reach the best state. The purpose of cement retarding is to ensure that the tiny particles such as stone powder in the gabbro fine aggregate have sufficient time to be better infiltrated by water, while also avoiding the decrease in concrete volume stability caused by too rapid hydration. However, excessive retarding will affect the strength of concrete. Therefore, the optimal retarding time is 320-370min; the alkali content is controlled at 15%-16%, which is the best range after comprehensive consideration of the activity of the water reducer and the activity of the gabbro alkali.
[0018] In a preferred embodiment of the present invention, the air entraining agent is an alkyl alcohol ether amphiphilic liquid high-efficiency air entraining agent. Preferably, the air entraining amount of the air entraining agent is 4.5%-5.5%. This type of air entraining agent has a good compounding effect with the above-mentioned water reducer, and produces fine and stable microbubbles. Since the presence of fine particles such as fly ash and stone powder will affect the air entraining effect, in order to improve the construction workability and durability of gabbro RCC, the pore structure parameters are controlled. Further preferably, the dosage of this type of air entraining agent is controlled in the range of 0.35-0.45 / 10,000.
[0019] In a preferred embodiment of the present invention, the gabbro fine aggregate includes crushed stone with a particle size of 0.16-5mm and stone powder <0.16mm, the fineness modulus of the crushed stone with a particle size of 0.16-5mm is controlled at 2.5-3.4, the average particle size of the crushed stone with a particle size of 0.16-5mm is 0.4-0.5, and the stone powder content is 10% <25%.
[0020] According to the concrete performance and construction requirements, the fine aggregate grading and stone powder content can be adjusted to meet the standards while minimizing the crushing cost and waste conditions. According to the test, the fineness of the fine aggregate or the stone powder content has an important influence on the performance of the roller compacted concrete mixture and the hardened material. It is further preferred that the aggregate fineness modulus is controlled at 2.6-2.8, the stone powder content is between 18% and 22%, and the unit volume of the adhesive has the best effect on the compressive strength of the concrete. The aggregate fineness modulus is controlled at 2.6-3.2, and the stone powder content is between 20% and 22%. The ultimate tensile strength of the concrete reaches the maximum. The aggregate fineness modulus is controlled at 2.8-3.3 and the stone powder content is within the range of 15.3% to 23.8%, and the roller compacted concrete has the best antifreeze performance. The aggregate fineness modulus is controlled at 2.5-2.7, and the stone powder content is within the range of 17.1% to 21.8%, and the antifreeze performance is good.
[0021] In a preferred embodiment of the present invention, the gabbro coarse aggregate includes gabbro coarse aggregate with a particle size of 5-20 mm, gabbro coarse aggregate with a particle size of 20-40 mm, gabbro coarse aggregate with a particle size of 40-60 mm, and gabbro coarse aggregate with a particle size of 60-80 mm.
[0022] The gabbro coarse aggregate is prepared by mixing crushed stones with particle sizes of 5-20mm, 20-40mm, 40-60mm and 60-80mm in 2, 2.5 and 3 grades.
[0023] In a preferred embodiment of the present invention, the compact density of the 5-20 mm gabbro coarse aggregate is 1850-1900 kg / m 3 , compact porosity 36%-38%, 10-15mm gabbro coarse aggregate accounts for 65-70% of the 5-20mm gabbro coarse aggregate, and the firmness is 2%-2.5%; the compact density of the 20-40mm gabbro coarse aggregate is controlled at 1750-1800kg / m 3 , compact porosity 38%-40%, 25-35mm gabbro coarse aggregate accounts for 40-45% of the 20-40mm gabbro coarse aggregate, and the firmness is 2%-2.5%; the compact density of the 40-60mm gabbro coarse aggregate is controlled at 1725-1775kg / m 3 , compact porosity 40%-42%, 45-55mm particle size 42-46%, firmness 1.5%-2.0%; the compact density of the 60-80mm gabbro coarse aggregate is controlled at 1700-1725kg / m 3 , tight porosity 40%-42%, 65-75mm particle size accounts for 43-48%, and firmness 1.5%-2.0%.
[0024] Under this condition, gabbro RCC can reach the maximum bulk density while meeting the workability standard. When the density of 40-60mm or 60-80mm crushed stone is too large and the tight porosity is too small, the 50-20mm and 20-40mm crushed stone cannot fully fill the gaps between the large stones, resulting in a decrease in the bulk density of the concrete and a decrease in its durability and strength; and when the density of 40-60mm or 60-80mm crushed stone is too small and the tight porosity is too large, it will make it difficult for the workability of the concrete to meet the construction requirements; similarly, when the density of 5-20mm or 20-40mm crushed stone is too large and the tight porosity is too small, the fine aggregate cannot fully fill the gaps in the crushed stone, and vice versa, it will also cause insufficient workability of the concrete; the aggregate test specification only stipulates the upper limit of the firmness of the crushed stone, but it has been found through experiments that the smaller the firmness value, the higher the crushing difficulty and energy consumption, so the invention controls the lower limit of the firmness value of the crushed stone.
[0025] Compactness, or compactness, refers to the degree to which solid matter is filled in a material. Compactness and porosity are indicators that indicate two corresponding aspects of the same material.
[0026] In a preferred embodiment of the present invention, the mass ratio of the 5-20 mm gabbro coarse aggregate, the 20-40 mm gabbro coarse aggregate, the 40-60 mm gabbro coarse aggregate and the 60-80 mm gabbro coarse aggregate in the gabbro coarse aggregate is 25-35:40-30:15-20:15-20, and the tight porosity is 32%-33.5%. The gabbro coarse aggregate has a three-graded particle size, and the gabbro aggregate yield can reach 80%-95%.
[0027] In a preferred embodiment of the present invention, the fly ash belongs to Class II ash, has a fineness of ≤25.0%, and a water demand ratio of less than 105%.
[0028] The present invention also discloses a method for preparing the gabbro aggregate rolled concrete, comprising the following steps:
[0029] S1. crushing the gabbro;
[0030] S2, classifying and blending the gabbro aggregate obtained by crushing in S1 to obtain gabbro coarse aggregate and gabbro fine aggregate;
[0031] S3. Dry-mix the obtained gabbro coarse and fine aggregates with medium-heat silicate cement and fly ash in a weight ratio to obtain a mixture I, mix water, a water reducing agent and an air entraining agent to obtain a mixed solution II, mix the mixture I and the mixed solution II, stir and vibrate, and finally obtain the gabbro aggregate roller compacted concrete.
[0032] Among them, the graded blending described in S2 involves coarse and fine aggregates.
[0033] The coarse aggregate is mixed according to 2, 2.5 and 3 grades, among which, the 2 grade particle size is 5-20mm: 20-40mm at a mass ratio of 50-60: 50-40, and the tight porosity is controlled at 34%-35%; the 2.5 grade particle size is 5-20mm: 20-40mm: 40-60mm at a mass ratio of 25-35: 40-30: 30-40, and the tight porosity is controlled at 33.5%-34%; the 3 grade particle size is 5-20mm: 20-40mm: 40-60mm: 60-80mm at a mass ratio of 25-35: 40-30: 15-20: 15-20, and the tight porosity is controlled at 32%-33.5%.
[0034] Here, 2, 2.5, and 3 gradations are conventional coarse aggregate grading methods in this field. In order to meet the different performance requirements of concrete in different parts, it is often required that the mix design include concrete of multiple gradations. Compared with 2.5 and 2 gradations, 3 gradation contains 40-80mm particle size aggregate, which reduces the number of crushing times and energy consumption, and reduces the crushing loss.
[0035] Fine aggregate is a mixture of the above-mentioned aggregate ≥0.16mm and stone powder <0.16mm.
[0036] Among them, the proportional dry mixing described in S3 uses a self-falling mixer, and the mixing time is 110s-120s; the mixed stirring uses a self-falling mixer, and the mixing time is controlled at 120s-140s considering the stone powder dosage. When the stone powder dosage is 10%, the mixing time is 110s-120s, and the mixing time increases by 4-5s for every 2% increase in stone powder; the vibration time is controlled at 20s-30s to avoid separation of the slurry and the bone due to under-compaction or over-vibration.
[0037] The present invention greatly improves the utilization rate of raw materials and reduces the generation of by-products by means of crushing scheme design and the like.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The present invention provides a new idea and method for preparing concrete aggregate: the preparation of gabbro as concrete aggregate has problems such as poor aggregate particle shape, particle size grading, and alkali activity. The present invention provides a reference for the preparation technology of such aggregate. The performance of the gabbro aggregate roller compacted concrete mixture, concrete strength, deformation performance, frost resistance grade and durability of the present invention all meet the standard.
[0040] (2) Reduce costs and energy consumption: The traditional method of using gabbro as aggregate requires crushing it into small pieces of gravel. However, this method uses graded crushing and reasonable mixing to use gabbro as coarse and fine aggregate for concrete, which greatly reduces the number of crushing times, reduces energy consumption and costs. In addition, gabbro is widely distributed and easy to obtain, with significant economic benefits, and is suitable for promotion and application. DETAILED DESCRIPTION
[0041] The present invention will be further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited to the scope of the examples. These examples are only used to illustrate the present invention, but not to limit the scope of the present invention.
[0042] Example 1
[0043] In this embodiment, the composition content of the gabbro is 45% SiO2, 3.6% K2O, 2.4% Na2O; and the content of ferromagnesian minerals is 50%.
[0044] The invention discloses a gabbro aggregate roller compacted concrete, which comprises the following components by weight: 85 parts of medium-heat silicate cement, 100 parts of fly ash, 1480 parts of gabbro coarse aggregate, 800 parts of gabbro fine aggregate, 1.1 parts of water reducing agent, 0.15 parts of air entraining agent and 93 parts of mixing water.
[0045] The cement fineness is controlled at a specific surface area of 321m 2 / kg, the hydration calorific value at 3d is controlled at 250kJ / kg, at 7d is 269kJ / kg, the time for hydration temperature rise to reach the temperature peak is controlled at 12 hours, and the cement alkali content is controlled at 0.44%.
[0046] The fly ash belongs to Class II ash, with a fineness of 10.1%, a water requirement ratio of 102%, a Fe2O3 mass proportion of 5.42%, an Al2O3 mass proportion of 14.56%, and a CaO and MgO mass proportion of 3.6%.
[0047] The gabbro coarse aggregate is prepared by mixing crushed stones with particle sizes of 5-20mm, 20-40mm, 40-60mm and 60-80mm, among which the compact density of 5-20mm crushed stones is 1870kg / m 3 , compact porosity 37%, 10-15mm particle size 68%, firmness 2%; among which 20-40mm crushed stone compact density is controlled at 1780kg / m 3 , compact porosity 39%, 25-35mm particle size 43%, firmness 2%; the compact density of 40-60mm crushed stone is controlled at 1750kg / m 3 The compact porosity is 41%, the particle size of 45-55mm accounts for 44%, and the firmness is 1.7%; the compact density of 60-80mm crushed stone is controlled at 1720kg / m 3 , tight porosity 41%, 65-75mm particle size 45%, firmness 1.5%.
[0048] The gabbro fine aggregate is made of crushed stone with a particle size of 0.16-5 mm and stone powder, the fineness modulus is controlled at 3.09, the average particle size is 0.47, and the stone powder content is 20%.
[0049] The water reducer is a powdered slow-setting high-efficiency water reducer with a fineness of 6.5%, a slow-setting time of 350 min, a water reduction rate of 19%, a water bleeding rate of 36.2%, a total alkali content of 15.67%, and a shrinkage rate of 113%. In this embodiment, the high-efficiency water reducer adopts the JM-Ⅱ slow-setting high-efficiency water reducer produced by Subot.
[0050] The air entraining agent is an alkyl alcohol ether amphiphilic liquid high-efficiency air entraining agent, with an air entraining amount of 4.6% and a dosage of 0.4 / 10,000 parts. In this embodiment, the air entraining agent is Subot GYQ-Ⅰ air entraining agent.
[0051] The method for preparing the gabbro aggregate roller compacted concrete comprises the following steps:
[0052] The crushed gabbro aggregate is graded and blended to obtain gabbro coarse aggregate and gabbro fine aggregate. The coarse aggregate is blended in three grades, with particle sizes of 5-20mm: 20-40mm: 40-60mm: 60-80mm in a mass ratio of 30:40:15:15, and the tight porosity is controlled at 33%. The fine aggregate is a mixture of the above-mentioned aggregate ≥0.16mm and stone powder <0.16mm.
[0053] The obtained gabbro coarse and fine aggregates were dry-mixed with other concrete raw materials in proportion for 120 seconds to obtain a mixture, water, water reducer and air entraining agent were mixed in order to obtain a mixed solution, the above two mixtures were mixed and stirred for 140 seconds and then vibrated for 25 seconds to finally obtain gabbro aggregate roller compacted concrete, and the mixture performance, concrete strength, deformation performance and durability of the gabbro aggregate roller compacted concrete were tested, and the results are shown in Tables 1.1-1.4 respectively.
[0054] Table 1.1 Test results of performance of RCC mixture
[0055]
[0056] Table 1.2 RCC strength test results
[0057]
[0058] Table 1.3 Test results of ultimate tensile strength and elastic modulus of RCC
[0059]
[0060] Table 1.4 Test results of anti-seepage and anti-freeze performance of RCC
[0061]
[0062] Comparative Example 1
[0063] The difference is that the chemical composition of fly ash is different, Fe2O3 accounts for 4.21% by mass, Al2O3 accounts for 10.65% by mass, and CaO and MgO account for 3.04% by mass. The rest is the same as Example 1. The air content and early strength of concrete are not much different from those of Example 1, and the deformation performance and durability results are shown in Tables 2.1-2.2 respectively
[0064] Table 2.1 Test results of ultimate tensile strength and elastic modulus of RCC
[0065]
[0066] Table 2.2 Test results of anti-seepage and anti-freeze performance of RCC
[0067]
[0068] Comparing 1.3 and 2.1, we can see that Fe2O in fly ash 3、 Al2O 3、 The reduction in the content of CaO and MgO leads to a decrease in the ultimate tensile strength and elastic modulus of concrete. This is because the corresponding metal oxides in fly ash can effectively inhibit the alkali activity of aggregate and thus greatly increase the volume stability of concrete. By comparing 1.4 and 2.2, it can be seen that the durability of concrete in Example 1 has also decreased.
[0069] Comparative Example 2
[0070] The difference is that the water reducing agent is a general high-efficiency water reducing agent, and the rest is the same as Example 1. The water reducing agent used in this comparative example is a polycarboxylic acid powdered water reducing agent produced by Nigo Technology Co., Ltd., model PC508.
[0071] The differences in RCC mixture properties and concrete strength compared with Example 1 are shown in Tables 3.1 and 3.2.
[0072] Table 3.1 Test results of performance of RCC mixture
[0073]
[0074] Table 3.2 RCC strength test results
[0075]
[0076] It can be seen that the addition of slow-setting water-reducing agent delays cement hydration and thus increases the mid- and late-stage strength of concrete. Field tests show that slow-setting water-reducing agent has a good effect on improving the workability of gabbro RCC, can effectively reduce the amount of cement used, and improves the volume stability of concrete by reducing the early heat release of cement.
[0077] Comparative Example 3
[0078] The difference is that a general air entraining agent is added, and the rest is the same as Example 1. The air entraining agent used in this comparative example is GYQE100 air entraining agent produced by Subot.
[0079] The concrete mixture performance and durability test results are shown in Tables 4.1 and 4.2.
[0080] Table 4.1 Test results of performance of RCC mixture
[0081]
[0082] Table 4.2 Test results of anti-seepage and anti-freeze performance of RCC
[0083]
[0084] By comparison, it can be seen that after adding general air-entraining agent, the VC value increases significantly, the air content decreases, and it is not easy to construct; due to the lack of air-entraining agent to introduce uniform small bubbles, the antifreeze performance is reduced, and the antifreeze grade only reaches F80, but the concrete is denser, and the compressive strength and elastic modulus are slightly improved.
[0085] Comparative Example 4
[0086] The difference is that the amount of stone powder added is 10%, and the rest is the same as Example 1.
[0087] The test results of gabbro aggregate RCC mixture properties, concrete strength, deformation properties and durability are shown in Tables 5.1-5.4 respectively.
[0088] Table 5.1 Test results of performance of RCC mixture
[0089]
[0090] Table 5.2 RCC strength test results
[0091]
[0092] Table 5.3 Test results of ultimate tensile strength and elastic modulus of RCC
[0093]
[0094] Table 5.4 Test results of anti-seepage and anti-freeze performance of RCC
[0095]
[0096] By comparison, it can be seen that the stone powder content has a great influence on the fluidity, air content, concrete strength, deformation performance and durability of concrete. However, when the stone powder content is reduced from 20% to 10%, the strength, ultimate tensile strength and elastic modulus of concrete all decrease significantly, and even the frost resistance grade drops to F75, which does not meet the design technical requirements.
[0097] Comparative Example 5
[0098] The difference is that the compact density and porosity of the 40-60 mm particle size crushed stone of the coarse aggregate are different. The others are the same as in Example 1, where the compact density of the 40-60 mm crushed stone is controlled at 1850 kg / m 3 , tight porosity 35%. The test results of gabbro aggregate RCC mixture properties, concrete strength, and durability are shown in Tables 6.1-6.3 respectively.
[0099] Table 6.1 Test results of performance of RCC mixture
[0100]
[0101] Table 6.2 RCC strength test results
[0102]
[0103]
[0104] Table 6.3 Test results of anti-seepage and anti-freeze performance of RCC
[0105]
[0106] By comparison, it can be seen that when the density of 40-60mm crushed stone is too large and the tight porosity is too small, the fluidity of the concrete mixture becomes poor, the bulk density decreases, and the overall strength of the concrete decreases accordingly. At the same time, the concrete's impermeability and frost resistance level also decreases.
Claims
1. A gabbro aggregate rolled concrete, characterized in that The invention comprises the following components in parts by weight: 65-105 parts of medium-heat silicate cement, 80-120 parts of fly ash, 1280-1680 parts of gabbro coarse aggregate, 700-900 parts of gabbro fine aggregate, 0.8-1.4 parts of water reducing agent, 0.1-0.2 parts of air entraining agent, and 73-113 parts of water; The time for the hydration temperature rise of the medium-heat silicate cement to reach the temperature peak is 10-14 hours; In the fly ash, Fe2O3 accounts for 5%-8% by weight, Al2O3 accounts for 12%-16% by weight, and CaO and MgO account for 4%-6% by weight.
2. The gabbro aggregate roller compacted concrete according to claim 1, characterized in that: The specific surface area of the medium-heat silicate cement is ≥250m 2 / kg, the cement alkali content is controlled at 0.3%-0.6%.
3. The gabbro aggregate roller compacted concrete according to claim 1, characterized in that: The water reducing agent is a powdered slow-setting high-efficiency water reducing agent.
4. The gabbro aggregate roller compacted concrete according to claim 1, characterized in that: The air entraining agent is an alkyl alcohol ether type amphiphilic liquid high-efficiency air entraining agent.
5. The gabbro aggregate roller compacted concrete according to claim 1, characterized in that: The gabbro fine aggregate includes crushed stone with a particle size of 0.16-5mm and stone powder with a particle size of less than 0.16mm. The fineness modulus of the crushed stone with a particle size of 0.16-5mm is controlled at 2.5-3.4, the average particle size of the crushed stone with a particle size of 0.16-5mm is 0.4-0.5, and the amount of stone powder is less than 10% and less than 25%.
6. The gabbro aggregate roller compacted concrete according to any one of claims 1 to 5, characterized in that: The gabbro coarse aggregate includes 5-20 mm gabbro coarse aggregate, 20-40 mm gabbro coarse aggregate, 40-60 mm gabbro coarse aggregate and 60-80 mm gabbro coarse aggregate.
7. The gabbro aggregate roller compacted concrete according to claim 6, characterized in that: The compact density of the 5-20 mm gabbro coarse aggregate is 1850-1900 kg / m 3 , compact porosity 36%-38%, 10-15mm gabbro coarse aggregate accounts for 65-70% of the 5-20mm gabbro coarse aggregate, and the firmness is 2%-2.5%; the compact density of the 20-40mm gabbro coarse aggregate is controlled at 1750-1800kg / m 3 , compact porosity 38%-40%, 25-35mm gabbro coarse aggregate accounts for 40-45% of the 20-40mm gabbro coarse aggregate, and the firmness is 2%-2.5%; the compact density of the 40-60mm gabbro coarse aggregate is controlled at 1725-1775kg / m 3 , compact porosity 40%-42%, 45-55mm particle size 42-46%, firmness 1.5%-2.0%; the compact density of the 60-80mm gabbro coarse aggregate is controlled at 1700-1725kg / m 3 , tight porosity 40%-42%, 65-75mm particle size accounts for 43-48%, and firmness 1.5%-2.0%.
8. The gabbro aggregate roller compacted concrete according to claim 6, characterized in that: The mass ratio of the 5-20 mm gabbro coarse aggregate, the 20-40 mm gabbro coarse aggregate, the 40-60 mm gabbro coarse aggregate and the 60-80 mm gabbro coarse aggregate in the gabbro coarse aggregate is 25-35:40-30:15-20:15-20, and the tight porosity is 32%-33.5%.
9. A method for preparing the gabbro aggregate roller compacted concrete according to any one of claims 1 to 8, characterized in that The following steps are involved: S1. crushing the gabbro; S2, classifying and blending the gabbro aggregate obtained by crushing in S1 to obtain gabbro coarse aggregate and gabbro fine aggregate; S3. Dry-mix the obtained gabbro coarse and fine aggregates with medium-heat silicate cement and fly ash in a weight ratio to obtain a mixture I, mix water, a water reducing agent and an air entraining agent to obtain a mixed solution II, mix the mixture I and the mixed solution II, stir and vibrate, and finally obtain the gabbro aggregate roller compacted concrete.
Citation Information
Patent Citations
A kind of ultra-high fly ash content concrete
CN105731919B